Review on carbon fiber reinforced polymer (CFRP) and their mechanical performance. (2019) - Hegde, Sharun; Satish Shenoy, B.; Chethan, K.N.
Abstract: Materials play a huge role in the shaping and development of human civilization. The need for materials started from the early stone-age where man needed fire to keep him warm and also to cook his food. Many materials such as copper, iron have been used in the past for few of the applications. But with the advancement of technology and new innovations brings about the need for lighter, more compact and many such other properties. So in order to fulfill these conditions a material such as composite material was developed. Carbon fiber Reinforced Polymer (CFRP) is a composite material which is very unique. CFRP has been widely used in aerospace industries. Slowly but gradually due to reduction in cost has lead it to be introduced in the automobile sector. The strength of the CFRP depends on the type of application, right combination of fiber to resin, length, type, orientation of fibers, use of anchors and form (sheet, plate). Temperature is an important factor which is taken into consideration. Curing of the adhesive at elevated temperatures and also if temperatures of the structures to which CFRP are bonded are kept below the glass transition temperature (Tg ) it leads to longevity of the structure. CFRP is not affected by moisture by using non-reactive adhesive and in certain cases by treating the specimen with silane. The machinability of the CFRP specimens can be accomplished by using cold air, cryogenic environments and also by traditional methods with slight modifications. Hence it can be found useful in construction industry.